Changing Trends in International Versus Domestic HCV Transmission in HIV-Positive Men Who Have Sex With Men: A Perspective for the Direct-Acting Antiviral Scale-Up Era. (13th February 2019) - Salazar-Vizcaya, Luisa; Kouyos, Roger D; Metzner, Karin J; Caraballo Cortes, Kamila; Böni, Jürg; Shah, Cyril; Fehr, Jan; Braun, Dominique L; Bernasconi, Enos; Mbunkah, Herbert A; Hoffmann, Matthias; Labhardt, Niklaus; et al.
Abstract: Background: Scale-up of direct-acting antiviral therapy is expected to abate hepatitis C virus (HCV) incidence among human immunodeficiency virus (HIV)-positive men who have sex with men (MSM). International transmission could influence this process. We classified HCV infections in HIV-positive MSM as either domestically or internationally acquired, and estimated how this classification changed over time. Methods: HCV subtype 1a (the most frequent subtype among MSM) genomes from 99 persons enrolled in the Swiss HIV Cohort Study and diagnosed with replicating HCV infections, were sequenced. Sixty-six of these sequences were from MSM. We inferred maximum-likelihood phylogenetic trees and time trees containing a fragment of the NS5B region of these and 374 circulating strains. We inferred transmission clusters from these trees and used the country composition of such clusters to attribute infections to domestic or international transmission. Results: Of HCV transmissions, 50% to 80% were classified as domestic depending on the classification criterion. Between 2000 and 2007, the fraction attributable to domestic transmission was 54% (range 0–75%). It increased to 85% (range 67%–100%) between 2008 and 2016. Conclusions: International and domestic transmission have played major roles in this epidemic. While international transmission persists, local transmission has established as the main source of infections. Abstract : We used phylogenetics and phylodynamics to classify over time HCV infections in HIV-positive MSM as either domestically or internationally acquired. We found that while international transmission dominated initially and persists, local transmission has established as the main source of infections.